Identifying methodological challenges in the social risk assessment of cellulosic ethanol value chains. (24th May 2022) - Marting Vidaurre, Nirvana A.; Lewandowski, Iris; Lask, Jan
Abstract: Social risk assessment using databases allows sustainability practitioners' rapid identification of social hotspots in value chains. The Soca database for sustainability assessment allows practitioners to perform a social risk assessment in addition to environmental assessment. As it is based on Ecoinvent, a database for environmental appraisal, the Soca database provides limited regionalization of data. This study aims to perform a regionalized assessment at country‐level by following the Soca approach in combination with EXIOBASE 3 as a source of regional information on the origin of inputs and for the estimation of worker hours. This analysis uses a case study based on the production of advanced biofuels in Croatia to assess the shortcomings of the methodology. We show that the assumptions made during the study can lead to unspecific results and that results need to be validated by external sources of information. Data availability plays a crucial role in achieving usable results. Social hotspots result from the combination of worker hours, raw material requirements, and social conditions in the country where production takes place. These three factors and the assumptions made need to be presented in a clear and transparent way to facilitate the interpretation of results.